Phytosome: A Novel Approach to Enhance the Bioavailability of Phytoconstituent - Nanavati, Dr. Bhanuben (Asian Journal of Pharmaceutics (AJP), 2017)
Novel drug delivery systems have gained significant importance because of their enhanced bioavailability and overall therapeutics. Hydrophilic nature and unique chemical structure of most of the therapeutically useful phytoconstituents which result in poor bioavailability and less absorption. The water soluble phytoconstituents have excellent bioactivity in vitro, but less or no action in vivo. Phytosome technology can overcome this problem in which the phytoconstituent is allowed to react with phospholipid. The phytoconstituent with poor lipid solubility on complexation into phytosome, can exhibit better pharmacodynamics and pharmacokinetics profile as compared to conventional herbal extract. Phytoconstituent must have good hydrophilicity which helps in dissolution in gastrointestinal fluid and hydrophobicity which helps cross lipid-rich cell membrane. Phytosome technology results in an intermolecular bonding between phospholipid, phosphatidylcholine and a single molecule of phytoconstituent. Phosphatidylcholine used in phytosome technology has also proven its clinical efficacy by acting as a carrier for fat and water miscible nutrients and natural digestive aid. Phytosomes can be used to treat acute and chronic liver failure due to improved pharmacological and pharmacokinetic property. In market, many products based on phytosome technology are available which include herbal extracts and phytochemicals with great therapeutic potential such as curcumin, ginkgo biloba, grape seed, silymarin, and many more. The present review highlights the method of preparation, properties, advantages, characterization, and applications.